2021
DOI: 10.3390/ijerph182312583
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Preference Differences between Elderly and Younger Exergame Users

Abstract: Existing motion capture technology can efficiently track whole-body motion and be applied to many areas of the body. This whole-body interaction design has gained the attention of many researchers. However, few scholars have studied its suitability for elderly users. We were interested in exercise-based whole-body interactive games, which can provide mental and physical exercise for elderly users. We used heuristic evaluation to measure participants’ actions during exergame tasks and analyzed preference differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Older adults are motivated more by perceived health effects, the pleasure of the game, and the improvement of social confidence [ 20 , 54 ]. Wang et al [ 55 ] suggested that when designing exergames, first, aging characteristics should be included, paying attention to the decline of cognitive and physiological abilities associated with aging. Second, the game motion recognition should have higher fault tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Older adults are motivated more by perceived health effects, the pleasure of the game, and the improvement of social confidence [ 20 , 54 ]. Wang et al [ 55 ] suggested that when designing exergames, first, aging characteristics should be included, paying attention to the decline of cognitive and physiological abilities associated with aging. Second, the game motion recognition should have higher fault tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…On one hand, there is a more active, healthy view of old age with more community participation [ 5 , 6 , 7 ]. On the other hand, the presence of digital technologies has emerged as a disturbing and conditioning element for the functional development of elderly people as they experience difficulties in their access and use [ 8 , 9 ], a fact that increases the generational digital gap [ 10 , 11 ], social inequality [ 12 , 13 , 14 ], and differences compared to other age groups [ 15 ].…”
Section: Introductionmentioning
confidence: 99%